Relaparotomy: review of indications and outcome in tertiary care hospital - Srivastava, Prachi; Qureshi, Sabuhi; Singh, Uma (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Relaparotomy is a rare complication after surgery associated with significant morbidity and mortality. Inappropriate selection of patients for relaparotomy, especially those who will not clearly benefit from surgery can be deleterious. This study was thus, planned to identify the indications, procedure, risk factors and outcomes of relaparotomy. Methods: This was a retrospective cohort study conducted in department of Obstetrics and Gynaecology, King George’s Medical University from January 2008 to January 2014. Results: 19 cases of relaparotomy were identified. 17 patients (89.5%) had emergency primary surgery while 2 (10.5%) had elective surgery. Majority of patients required relaparotomy in view of hemorrhage (63.15%) followed by burst abdomen (31.5%) and bowel injury (5.26%). Obstructed labor was the major indication of primary surgery in patients operated for burst abdomen while placenta previa was the major indication of primary surgery in patients operated for PPH. Increased duration of hospital stay, requirement of blood transfusion and incidence of post-operative fever and sepsis was seen in patients undergoing relaparotomy. Out of 19 patients, 3 (15.7%) patients died. Conclusions: Relaparotomy is a rare condition which surgeon might have to encounter. However, ensuring proper hemostasis and asepsis during surgical procedures can reduce the incidence of relaparotomy. Calculative decision before embarking on relaparotomy can decrease the incidence of morbidity and mortality associated with the procedure.